Local and geographic variation in grazing intensity by herbivorous crabs in SW Atlantic salt marshes - Alberti, J. (2007)
Coupling experiments at small spatial scales with large-scale surveys can help to generalize experimental results across large spatial scales. The goal of the present study was to evaluate patterns of crab herbivory within and, at a larger scale, between many southwestern (SW) Atlantic salt marshes. Hence, we conducted experiments in an Argentinean salt marsh to elucidate the effects of crab Chasmagnathus granulatus grazing on the cordgrass Spartina densiflora and the factors that can affect this interaction, and then examined the potential generality of these results across SW Atlantic salt marshes from Brazil to Argentina (15 marshes, range ≈ 2000 km). Experimental examination of the effects of crabs (control and exclusion) on marsh grass transplants, and factors that can affect them, i.e. the presence or absence of plant neighbors and marsh height (middle and low), revealed that crab herbivory decreased plant biomass and increased stem mortality; however, herbivory effects were significantly diminished in the presence of plant neighbors and with increasing marsh elevation. Our geographical survey showed that crab herbivory is common in SW Atlantic salt marshes, with more than 20 % of leaves damaged in most marshes and with greater consumption at marshes with higher crab densities. In addition, plants at the lower edge of marshes were generally the most consumed (max. >60 % leaves consumed) and crabs preferred S. alterniflora over S. densiflora. Over a regional spatial scale, our results suggest that herbivory may affect plant production at some marshes and can also play a role in limiting the lower tidal elevation limit of low-marsh plants. © Inter-Research 2007.